Evaluación del tiempo de referencia de II a III nivel de atención del servicio de pediatría en la unidad de servicios de salud de Bosa y el Hospital San Rafael de Fusagasugá y las variables que influyen en el período de Enero de 2015 a Diciembre de 2016 (2017)
The Reference and Counter-Reference System, is the set of processes, procedures and technical activities that allow an adequate provision of health services that ensure quality, accessibility, opportunity, continuity and integrity. Objective: To evaluate the reference time from II through III level of attention of the pediatric service in the center of health services located in Bosa and the San Rafael Hospital of Fusagasuga during the period between January of 2015 and December of 2016. Methods and Materials: A multicenter observational, descriptive and cross-section study was conducted to analyze the different variables that influence within the time of reference. Outcome and Conclusions: The remission time in both hospitals was carried out in a less time or equal to one day in most cases. It was observed that the variables of sex and age did not influence the time of remission, and that the new health system in the USS of Bosa did not remitted as many patients to the Subnetwork as it was expected, a relationship was evidenced between the time and service of destination, since patients were remitted in a shorter time due to the severity of their condition and that a high percentage of cancellation was secondary to a health betterment. Recommendations: Continue with this type of research to increase the bibliography regarding the subject and to elaborate more studies beyond the pediatric population. Establish a regulation to standardize a time of remission